Implementation of the AISMA Method to Improve the Beginning Reading Ability of Class I Students at Muhammadiyah Nurul Ilmi Elementary School Karangdowo - Eggi Mega Rahmawati; Supriyanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study was to determine the ability of beginning reading for grade I students at SD Muhammadiyah Nurul Ilmi Karangdowo who had difficulty reading after using the AISMA method in the 2022/2023 academic year. In this study the author used class action research. Data collection techniques used were observation, tests and documents. Data analysis techniques with comparative descriptive and critical analysis. To test the validity of the data, triangulation techniques were used. The conclusion of this research is that the use of the AISMA method can improve the ability of beginning reading for first grade students at SD Muhammadiyah Nurul Ilmi Karangdowo in the 2022/2023 academic year.